PENGARUH KOMUNIKASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA PADA DINAS KOPERASI, USAHA KECIL DAN MENENGAH KOTA MAKASSAR - Hendra Gunawan (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2022)
This study analyzes the effect of work communication and work environment on employee performance through work motivation at the Department of Cooperatives, Micro, Small and Medium Enterprises of Makassar City. The study applied a quantitative approach with an explanatory survey design. The sample consisted of 115 employees. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that work communication has a positive and significant effect on work motivation and employee performance. The work environment also has a positive and significant effect on work motivation and employee performance. Work motivation positively and significantly affects employee performance and mediates the effects of work communication and work environment on employee performance. These findings show that improving public employee performance cannot rely solely on formal work systems, but requires clear communication flows, a supportive work environment, and strong work motivation. This study contributes to the development of public sector human resource management studies, particularly in local government agencies responsible for strengthening cooperatives and small and medium enterprises.